Application of Chitosan and Omega-3 Supplementation on Blood Constituents, Immunity, and Antioxidant Enzymes in Broiler Chicks - Abdul-Rahman, Doaa I.M.; Hassan, Mostafa F.M.; Khalil, Waleed F.; Ahmed, Eman A.; Youssef , Fatma M.A. (Journal of Advanced Veterinary Research, 2023)
This experiment investigated the impact of chitosan (CHI), omega-3, and CHI as a delivery system for omega-3 on blood constituents, immunity, and antioxidant enzymes, in broiler chicks. Eighty (one-day-old) broiler chicks were assigned to four groups, each with 20 chicks (two replicates of 10 chicks each). The first group was a control group that did not receive any supplementation, while the other groups received different treatments, such as CHI or omega-3, either alone or in combination (over a peroid of 42 days). The results showed that all the supplemented groups had improved immune systems, as evidenced by higher white blood cell counts, lymphocyte percentages, and lower heterophil, and lymphocyte ratios. Additionally, the supplemented groups had higher levels of serum protein fractions, immunoglobulins, and antibody titer against ND and AI viruses. Furthermore, the study revealed that the supplemented groups had an increase in the bursa of Fabricius index, spleen index, and thymus index at both 28 and 42 days. The SOD and GSH serum levels also increased significantly in the supplemented groups. In conclusion, using CHI and omega-3 as a delivery system in broiler chicks had beneficial effects on blood constituents, immunity, and antioxidant enzymes, in broiler chicks.